A new high resolution computed tomography scoring system for pulmonary fibrosis, pleural disease, and emphysema in patients with asbestos related disease. Issue 2 (February 1992) - Jarad, N A; Wilkinson, P; Pearson, M C; Rudd, R M
Abstract : The aim of this study was to describe a scoring system for high resolution computed tomographic (HRCT) scans analogous to the International Labour Office (ILO) scoring system for plain chest radiographs in patients with asbestos related disease. Interstitial fibrosis, pleural disease, and emphysema were scored, the reproducibility and the interobserver agreement using this scoring system were examined, and the extent of the various types of disease was correlated with measurements of lung function. Sixty asbestos workers (five women and 55 men) mean age 59 (range 34-78) were studied. The lungs were divided into upper, middle, and lower thirds. An HRCT score for the extent of pleural disease and pulmonary disease in each third was recorded in a way analogous to the International Labour Office (ILO) method of scoring pleural and parenchymal disease on chest radiographs. A CT score for the extent of emphysema was also recorded. Pleural disease and interstitial fibrosis on the plain chest radiographs were assessed according to the ILO scoring system. A chest radiographic score for emphysema analogous to that used for HRCT was also recorded. Two independent readers assigned HRCT scores that differed by two categories or less in 96%, 92%, and 85% compared with 90%, 78%, and 79% of cases for chest radiographs for fibrosis, emphysema, and pleural disease respectively. There was better intraobserver repeatability for the HRCT scores than for the chest radiograph scores for all disorders. Multiple regression analysis showed that scores for interstitial fibrosis, emphysema, and pleural disease on chest radiographs and HRCT correlated to a similar degree with impairment of lung function.